2002
DOI: 10.1136/bjo.86.8.920
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of perforating ocular injuries in children

Abstract: Aims: To assess the aetiological factors associated with the occurrence of perforating ocular injuries in children in an urban setting and to assess the visual outcomes of such injuries. Methods: All cases of perforating ocular injury presenting to a single paediatric hospital (age less than 16 years) over a 17 year period were identified by a medical record search. All new cases of perforating ocular injury identified were included. All information was obtained retrospectively from the medical records. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
91
3
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 15 publications
20
91
3
11
Order By: Relevance
“…The incidence of injuries caused by motor vehicle accident is at 1% very low in comparison with that found by other studies. 9,11,20,21 This may be explained by little traffic in the predominantly rural areas we studied, and by the use of public transportation by most of the children.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The incidence of injuries caused by motor vehicle accident is at 1% very low in comparison with that found by other studies. 9,11,20,21 This may be explained by little traffic in the predominantly rural areas we studied, and by the use of public transportation by most of the children.…”
Section: Discussionmentioning
confidence: 94%
“…However, the lack of supervision is not restricted to developing countries as has already been pointed out in recent studies from the western world. [8][9][10][11] Visual outcome and prognosis is expected to improve with prompt medical examination and therapy. However, socioeconomic, geographic, and cultural factors may keep patients from receiving timely and appropriate medical assistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported that 20-50% of ocular injury admissions are children. [11][12][13] Using the eye injury registry databases of the United States and Hungary, Kuhn et al 9 developed the ocular trauma score (OTS) in 2002, a simplified categorical system for standardized assessment and visual prognosis in ocular injuries (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…This difference was because playing behaviour of Indian children was different from Australian children. 11 …”
Section: Discussionmentioning
confidence: 99%